2019
DOI: 10.3389/fpsyg.2019.01096
|View full text |Cite
|
Sign up to set email alerts
|

Self-Construal Priming Modulates Ensemble Perception of Multiple-Face Identities

Abstract: This study explored the modulatory role of independent/interdependent self-construal on ensemble perception. Two experiments were conducted to study the effect of self-construal on ensemble coding of multiple-face identities (Experiment 1) and dot size (Experiment 2) separately. Before the implicit ensemble perception task, participants in both experiments were either primed with independent or interdependent self-construal via a well-validated pronoun circle task, in which they were exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 63 publications
(86 reference statements)
2
2
0
Order By: Relevance
“…The effect of positive emotion was thus considerably smaller compared to the effect of negative emotion. The asymmetry was similar to a finding in Peng et al (2019), where little or no increase of endorsements of the set average was observed after the participants were primed to process relational/holistic information, yet the endorsements for this decreased clearly when they were primed to process non-relational/individual information. The unequal effects could in part be due to the cultural background of the samples in these studies.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The effect of positive emotion was thus considerably smaller compared to the effect of negative emotion. The asymmetry was similar to a finding in Peng et al (2019), where little or no increase of endorsements of the set average was observed after the participants were primed to process relational/holistic information, yet the endorsements for this decreased clearly when they were primed to process non-relational/individual information. The unequal effects could in part be due to the cultural background of the samples in these studies.…”
Section: Discussionsupporting
confidence: 82%
“…Effects in our study demonstrate that the same participants could undergo fairly minor induction and then display differential ensemble processes subsequently. This malleable aspect of ensemble perception has also been demonstrated previously through priming interdependent or independent self (Peng et al, 2019), or through global or local processing orientation (Peng at el. 2020).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Such a cultural difference could play a role in ensemble coding, because an ensemble requires a global orientation. The idea that global processing is conducive to ensemble perception was firstly proposed by Chong and Treisman (2003), and further studied in Treisman, (2005a, 2005b), Chong et al (2008) and Peng et al (2019). Additionally, patients with unilateral spatial neglect (Pavlovskaya et al, 2015) and congenital prosopagnosia (Robson et al, 2018) displayed deficiency in ensemble perception, which might due to their focused attention mechanism and related perception of local features (local processing orientation).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, various researchers in cognition employed pronoun circling task and successfully investigated the effect of the task on cognitive outcomes such as visual scenes (Choi et al, 2016), holistic face processing and face categorization (Liu et al, 2019)or face recognition (Peng, 2019). In line with Oyserman and Lee (2008), the pronoun circling task has a strong effect on both cognitive tasks (d= 0.51) and relationship-related issues (d= 0.51).…”
Section: Manipulation Failurementioning
confidence: 99%